2021
DOI: 10.1016/j.ejim.2021.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of post-COVID-19 symptoms in hospitalized and non-hospitalized COVID-19 survivors: A systematic review and meta-analysis

Abstract: Background : Single studies support the presence of several post-COVID-19 symptoms; however, no meta-analysis differentiating hospitalized and non-hospitalized patients has been published to date. This meta-analysis analyzes the prevalence of post-COVID-19 symptoms in hospitalized and non-hospitalized patients recovered from COVID-19 . Methods : MEDLINE, CINAHL, PubMed, EMBASE, and Web of Science databases, as well as medRxiv and bioRxiv preprint servers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

46
352
6
26

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 384 publications
(430 citation statements)
references
References 58 publications
46
352
6
26
Order By: Relevance
“…In another meta-analysis the sample included 15,244 hospitalized and 9,011 non-hospitalized patients. The results showed that 63.2%, 71.9% and 45.9% of the sample exhibited ≥one post-COVID-19 symptom at 30, 60, or ≥90 days after onset/hospitalization [14]. On the other hand, the prevalence of symptoms that remain 12 weeks after SARS-CoV-2 infection in patients non-hospitalized may be as small as 3.0%, based on tracking specific symptoms (tighter definition), to 11.7% based on the wider questionnaire which includes the questions about the 21-symptom list that was recently reported from 26,922 UK residents by The Office for National Statistics [15].…”
Section: Discussionmentioning
confidence: 98%
“…In another meta-analysis the sample included 15,244 hospitalized and 9,011 non-hospitalized patients. The results showed that 63.2%, 71.9% and 45.9% of the sample exhibited ≥one post-COVID-19 symptom at 30, 60, or ≥90 days after onset/hospitalization [14]. On the other hand, the prevalence of symptoms that remain 12 weeks after SARS-CoV-2 infection in patients non-hospitalized may be as small as 3.0%, based on tracking specific symptoms (tighter definition), to 11.7% based on the wider questionnaire which includes the questions about the 21-symptom list that was recently reported from 26,922 UK residents by The Office for National Statistics [15].…”
Section: Discussionmentioning
confidence: 98%
“…For patients following hospitalization fatigue, dyspnea, and cough were the most common symptoms at 90-day follow-up occurring in 38.5%, 33.3%, and 10.4% of patients, respectively. 9 Some studies also suggest that symptoms may persist long after recovery and up to 6 months among some patients. 10,11 For example, Huang et al (2021) have reported that in a mean follow-up of 186 days 76% of the patients still suffered from at least one symptom, most commonly fatigue or muscle weakness, with a higher risk for patients with severe disease.…”
Section: Introductionmentioning
confidence: 99%
“…In the meta-analysis of 21 studies including 47.910 individuals (hospitalized and not hospitalized), 80% of subjects with a confirmed COVID-19 diagnosis were reported to continue having at least one symptom beyond two weeks following acute infection [ 6 ]. The results of another meta-analysis showed that 63.2%, 71.9%, and 45.9% of the sample, including 15.244 hospitalized and 9.011 non-hospitalized patients, exhibited ≥one post-COVID-19 symptom at 30, 60, or ≥90 days after onset/hospitalization [ 7 ]. Kidney transplant recipients (KTR) recipients are a high-risk group for severe COVID-19, whose case fatality ratio may reach up to 30%, owing not only to their chronic immunosuppression, but also to older age and frequently associated comorbidities, including hypertension, diabetes mellitus, chronic kidney disease, and cardiovascular complications [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%